Mathematical Connection Ability viewed from Cognitive Style and Gender in the CONINCON Learning (Constructivism, Integrative & Contextual) - Maulida, Azwida Rosana; Suyitno, Hardi; Asih, Tri Sri Noor (Unnes Journal of Mathematics Education Research, 2021)
Students have different characteristics both in gender and cognitive style. This difference also has an impact on students' mathematical abilities, especially mathematical connection abilities. Mathematical concepts are related to each other. Mathematical connection skills can help students to link between mathematical concepts so that students do not learn them separately. The purpose of this study is to describe the ability of students' mathematical connections in terms of cognitive and gender styles in the CONINCON learning model. This research is a mixed-method type sequential exploratory research, which is a sequential combination of qualitative to quantitative. The population of this study was all students of class VIII of SMP Negeri 18 Semarang. The subject of this research is class VIII D as the experimental class using the CONINCON learning model and class VIII C as the control class. Taking research subjects based on reflective & impulsive cognitive style categories and male & female. The results showed that the results of mathematical connection ability in terms of cognitive and gender styles varied. This is shown from the 8 students studied, namely 2 students in the reflective male category, 2 students in the reflective female category, 2 impulsive male students, and 2 impulsive female students.